Is 30 The Magic Number? Issues In Sample Size Estimation - Sitanshu Sekhar Kar; Archana Ramalingam (Medsci Publications, 2013)
Research has become mandatory for career advancement of medical graduates. Researchers are often confounded by issues related to calculation of the required sample size. Various factors like level of significance, power of the study, effect size, precision and variability affect sample size. Also design issues like sampling technique and loss to follow up need to be considered before calculating sample size. Once these are understood, the researcher can estimate the required sample size using softwares like Open Epi. Correct estimation of sample size is important for the internal validity of the study and also prevents unnecessary wastage of resources.